Ab initio study of the mechanism of formation of a spiro-Sn-heterocyclic ring compound by the cycloaddition reaction of H2C=Sn: and ethylene - Tan Xiaojun; Lu Xiuhui (Journal of the Serbian Chemical Society, 2019)
X2C=Sn: (X = H, Me, F, Cl, Br, Ph, Ar…) are new species of chemistry. The cycloaddition reactions of X2C=Sn: is a new study field of stannylene chemistry. The mechanism of cycloaddition reaction of singlet H2C=Sn: with ethylene is studied for the first time using the MP2/GENECP (C, H in 6-311++G**; Sn in LanL2dz) method in this paper. From the potential energy profile, it could be predicted that the reaction has one dominant reaction channel. The reaction rule presented is that the 5p unoccupied orbital of tin in H2C=Sn: sidewise overlaps with the bonding π orbital of ethylene resulting in the formation of an intermediate. The instability of the intermediate makes it isomerise to a four-membered ring stannylene. As the 5p unoccupied orbital of the Sn atom in the four-membered ring stannylene and the π orbital of ethylene form a π→p donor–acceptor bond, the four-membered ring stannylene further combines with ethylene to form another intermediate, and this intermediate further isomerises to a spiro-Sn-heterocyclic ring compound. The Sn in the spiro-Sn-heterocyclic ring compound is combined with adjacent atoms by sp3 hybridization. The results of this study reveal the mechanism of cycloaddition reaction of X2C=Sn: with symmetric π-bond compounds.